Design and performance comparison of interconnection and damping assignment passivity-based control for vibration suppression in active suspension systems. (April 2021) - Sistla, Pramod; Figarado, Sheron; Chemmangat, Krishnan; Manjarekar, Narayan Suresh; Kallu Valappil, Gangadharan
This study presents the design of interconnection and damping assignment passivity-based control for active suspension systems. It is well known that interconnection and damping assignment passivity-based control's design methodology is based on the physical properties of the system where the kinetic and potential energy profiles are shaped, and asymptotic stability is achieved by damping injection. Based on the choice of control variables, special cases of the control law are derived, and tuning of the control law with the physical meaning of the variables is demonstrated along with their simulation results. The proposed control law is experimentally validated on a scaled model of a quarter-car active suspension system with different road profiles, varying load conditions, and noise and delay in the sensor measurements and actuator respectively. The results are compared with that of an uncontrolled system with linear quadratic regulator and sliding mode control.